Peran Guru PAK dalam Membentuk Karakter Peserta Didik Berdasarkan Ulangan 6:7-9 - Lomakai, Debi Yolanda; Padalani, Jean Putri; Bambangan, Malik (IAKN Tarutung, 2025)
The Role of Christian Religious Education Teachers in Shaping Students’ Character Based on Deuteronomy 6:7-9 The role of Christian Religious Education (CATE) teachers in shaping students' character is pivotal in the context of moral and spiritual education. This paper elucidates how Deuteronomy 6:7-9, which directs parents to educate their children in the ways of the Lord, can be applied within the formal education setting. Deuteronomy 6:7-9 emphasizes the importance of continuously educating children about God’s laws, both at home and in school. In this regard, CATE teachers play a key role as educational agents who help convey spiritual and moral values to students. CATE teachers have the responsibility not only to impart knowledge of the Christian faith but also to guide students in understanding and internalizing the moral values inherent in God's teachings. Through consistent and directed instruction, CATE teachers can help shape students' character in accordance with the principles outlined in Deuteronomy 6:7-9. In the modern education context, CATE teachers also serve as exemplary models in living out Christian values in everyday life. By being consistent and authentic examples, CATE teachers can inspire students to develop strong and responsible characters in line with God's teachings. Thus, this paper concludes that the role of CATE teachers in shaping students' character based on Deuteronomy 6:7-9 is highly significant. Through teaching, guidance, and good examples, CATE teachers can assist students in gaining a deep understanding of Christian values and applying them in their daily lives.